Is the Emerging Asian Stock Markets Really Predictable Based on the Operations and Information Management? - Roni Bhowmik; Shouyang Wang (International Journal of Supply Chain Management, 2019)
Abstract—This paper examines the weak-form of market efficiency for six emerging Asian markets by using daily, weekly and monthly indices data based on the information management. The returns are not normally distributed, because they are negatively skewed and leptokurtic, and also found conditional heteroscedasticity. Findings suggest that none of the sample markets follow Random-walk and hence all are weak-form efficient markets except South Korean Markets. Additionally, short-term variants of the technical trading rules have better predictive ability than long-term variants. The results also reveal that these markets do not follow the same trend; the prices predictability is not analogous in all the sample markets.